PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP HASIL BELAJAR BIOLOGI SISWA KELASVII SMPN 1 SASAK RANAH PASISIE TAHUN PELAJARAN 2013/2014 - Sari, Adek Fatma (STKIP PGRI Sumbar, 2014)
Biology is one of branch Natural Science (IPA) that underlie the development of science and technology. Inorder to achieve the goal of learning biology, biology is expected to be favored and preferred learning students.However the reality of biological subjects not be liked the students because most of students think it is difficult tounderstand the biology lesson. Students who do not like biology class due to lack of intereset of students towardsbiology the model in the learning process. Teachers only applying a speech method and practice in teaching andlearning, so that students tend to get bored by listening to the explanation from the teacher. This research aimed toexamine the effect of the application cooperative learning model talking stick type toward biology learning outcomes atVII grade students of SMPN 1 Sasak Ranah Pasisie academic year 2013/2014. This reseacrh is an experimentalresearch. The population in this research were VII grade students in the second semester SMPN 1 Sasak Ranah Pasisiethe academic year 2013/2014. The sampling technique used randomized control group postes design, where the researchsample in the experimental class were VII1 class with 31 students and the control class were VII2 class that totaling 30students. The instrument used is an objective test and analysis data by using the t test. The result from this research gotthe experimental class had an average value of 80.72 is higher than the average value of the control class 70.41. Theresult from data were analyzed by test, and obtained the price Thitung 4,64 Ttable 1,67. Thus Thitung> Ttable which means H1is accepted. It was cocluded that the application of cooperative learning model talking stick type can improve biologylearning outcomes at VII grade student of SMP N 1 Sasak Ranah Pasisie academic year 2013/2014.